An Approach of PFC in BLDC Motor Drives Using BLSEPIC Converter - Murugan M; Jeyabharath R; Sarankumar V (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper presents the analysis and design of on front end bridgeless single-ended primary-inductance converter (BLSEPIC) based power factor rectification, with output voltage regulation and high frequency isolation working in discontinuous conduction mode. The switching loss in VSI is minimized by an electronic commutation of Brushless DC motor (BLDCM) is used to operate in a low-frequency operation. To improve the efficiency, the diode bridge rectifier is replaced with the alternate bridgeless topologies which offers less conduction losses, advised by the international power quality standards, a wide range of speed control is obtained with improved power quality BLDC motor drive is proposed and simulated in MATLAB/SIMULINK. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7404